Pancasila internalization and implementation as a deradicalized effort in Indonesia (Research, Society and Development, 2020)
The issue of diversity has recently been challenged by the rise of religious radicalism and terrorism groups that can cause the splitting of national unity. In the context of Indonesia they want to replace the ideology of Pancasila into an ideology of religion by forming Indonesia into a Khilafah state. The rise of religious radicalism groups often lead to acts of intolerance and terrorism, both in various countries and in Indonesia. Various incidents of intolerance and acts of violence in the name of religion occur in various places in the world. These incidents cause dehumanization which is very degrading to human dignity. In addition to the rampant intolerance and terrorism in Indonesia there is also a tendency for the politicization of religion as a tool for practical politics. This has led to national divisions which can threaten the existence and continuity of the unitary state of the Republic of Indonesia (NKRI). The Pancasila ethics are the efforts to understanding the concepts of God in religions where the conditions of the population are compound, so tolerance in implementing the religious life can be happened among diverse community in Indonesia. Besides, it needed to revitalize the understanding of the deity that has a good culture in education, the Indonesian policy or acculturation of Pancasila value in Indonesian citizen. Therefore, by internalizing and implementing Pancasila Indonesia could become a large and developed nation.